Keabsahan dan Upaya Pembatalan Perjanjian Pinjaman Online Ilegal dalam Praktik Peradilan Perdata - Nikmah, Mi Afifah; Siregar, Zalfa Nadhifah Umaimah; Simarmata, Anggi Sri Haryati (Majelis: Jurnal Hukum Indonesia, 2026)
This research is motivated by the escalating prevalence of illegal online lending practices in Indonesia, which generate a multitude of legal problems, particularly those concerning the validity of loan agreements and debt collection practices. The simplicity of access through smartphone applications, rapid processing times often approved within minutes and minimal administrative requirements have rendered these services immensely popular among the public. However, this accessibility also paves the way for unlicensed providers to operate unchecked, preying on desperate borrowers. The study aims to analyze the legal validity of illegal online loan agreements pursuant to the Indonesian Civil Code (KUHPerdata) and regulations issued by the Financial Services Authority (Otoritas Jasa Keuangan, OJK). Additionally, it examines the legal position of debt collection from a civil law perspective. A normative juridical method is employed, utilizing statutory and conceptual approaches, with qualitative analysis of the data. The results demonstrate that illegal online loan agreements fail to fulfill the requirements for a valid contract, especially regarding the legal capacity of the parties and lawful cause, categorizing them as null and void by operation of law. Nevertheless, in practice, unlicensed providers continue debt collection efforts, frequently employing methods that violate the law, such as harassment and intimidation. This reveals a significant gap between legal norms and field implementation. The implications emphasize the critical need for robust law enforcement, enhanced consumer protection mechanisms, and stricter oversight of fintech lenders to establish legal certainty and justice for society.